Features of colloid-chemical synthesis of luminophors based on strontium aluminates activated by cerium and manganese iones - Shevchenko, Gvidona P.; Varapay, Natalia V.; Zhuravkov, Viktor A.; Abramovich, Ekaterina A.; Kovel, Ekaterina A.; Bokshyts, Yuliya V. (Journal of the Belarusian State University. Chemistry, 2024)
Using colloidal chemical synthesis of luminophors based on strontium aluminates activated by cerium and manganese iones (SrAl2O4 : Ce3+, Mn2+), the influence of precipitation conditions (pH, ratio of initial reagents, type of precipitant and temperature) on the phase composition of the final product and its spectral and luminescent properties in comparison with solid-phase synthesis was studied. The promising method for controlling the spectral properties of SrAl2O4 : Ce3+, Mn2+ samples by varying the conditions of their synthesis has been shown.